Influence of intergenotypic competition on multigenerational persistence of abiotic stress resistance transgenes in populations of Arabidopsis thaliana - Bigelow, Patrick J.; Loescher, Wayne; Hancock, James F.; Grumet, Rebecca (Evolutionary applications, 2018)
Reducing crop losses due to abiotic stresses is a major target of agricultural biotechnology that will increase with climate change and global population growth. Concerns, however, have been raised about potential ecological impacts if transgenes become established in wild populations and cause increased competitiveness of weedy or invasive species. Potential risks will be a function of transgene movement, population sizes, and fitness effects on the recipient population. While key components influencing gene flow have been extensively investigated, there have been few studies on factors subsequent to transgene movement that can influence persistence and competitiveness. Here, we performed multiyear, multigenerational, assessment to examine fitness effects and persistence of three mechanistically different abiotic stress tolerance genes: C‐repeat binding factor 3/drought responsive element binding factor 1a (CBF3/DREB1a); Salt overly sensitive 1 (SOS1); and Mannose‐6‐phosphate reductase (M6PR). Transgenic Arabidopsis thaliana overexpressing these genes were grown in pure populations and in competition with wild‐type (WT) parents for six generations spanning a range of field environment conditions. Growth, development, biomass, seed production, and transgene frequency were measured at each generation. Seed planted for each generation was obtained from the previous generation as would occur during establishment of a new genotype in the environment. The three transgenes exhibited different fitness effects and followed different establishment trajectories. In comparison with pure populations, CBF3 lines exhibited reduced dry weight, seed yield, and viable seed yield, relative to WT background. In contrast, overexpression of SOS1 and M6PR did not significantly impact productivity measures in pure populations. In competition with WT, negative fitness effects were magnified. Transgene frequencies were significantly reduced for CBF3 and SOS1 while frequencies of M6PR appeared to be subject to genetic drift. These studies demonstrate the importance of fitness effects and intergenotype competition in influencing persistence of transgenes conferring complex traits.